Characterization of the ageing process of one-component polyurethane moisture curing wood adhesive. (January 2017) - Clerc, Gaspard; Brülisauer, Martina; Affolter, Samuel; Volkmer, Thomas; Pichelin, Frédéric; Niemz, Peter
Abstract: The aging resistance of five different one-component polyurethane (1C-PUR) adhesives with different mechanical properties has been investigated. The glue layer has been modeled as a superposition of three different layers representing the pure adhesive layer, the interaction layer between the wood and the adhesive and the plain wood layer. The modification of the mechanical properties of each layer was studied with a specific specimen for each layer. Also, a comparative analysis between natural and artificial weathering was conducted. The artificial weathering consists of a cyclic hydro-thermic treatment (treatment A5 according to DIN EN 302-1). The influence of a long time (5 months) mid-range temperature (70 °C) treatment was tested. Additionally, Fourier transform infrared spectroscopy (FTIR) analyses were conducted to determine the hypothetical chemical modification of the bond line. Generally, the strength properties of the samples decreased with the duration of the artificial weathering. However, significant differences were observed between the adhesive of the same system, especially during the temperature treatment. Furthermore, no relevant chemical degradation of the bond line was measured after 5 years of natural weathering (tested from 10 mm thick glued samples). The chosen method found that in the majority of cases, the wood is the weak layer in the bond line. Therefore, for moisture and temperature solicitation, there are no reasons to doubt the durability of the 1C-PUR glue layer for long term use. Nevertheless, further investigations are needed to better characterize the life expectancy of the wood and adhesive interface layer and to establish the influence of parameters, such as UV-radiation, wood extractives and moisture-induced stress, on the life expectancy of the bond line.